(untitled) (International Journal of Business, Economics and Management, 2016)
Customers are always surrounded by the media and advertising in their daily lives. These tactics are used to get the customer engagement towards the program, video or advertisement. Engagement with understanding the complete message of it called transportation. This research is conducted to examine the effects of media, transportation, advertising transportation on customer responsiveness. For this purpose, an ad is placed in between the video for the respondents. Target respondents are the students and the general public. Primary data is collected from above two hundred eighty seven respondents in Sahiwal via questionnaires. The results show that advertising transportation has the more significant effect on the customers’ responsiveness.